Salt-Inducible Kinase 2: An Oncogenic Signal Transmitter and Potential Target for Cancer Therapy - Chen, Fangyu; Chen, Liuwei; Qin, Qin; Sun, Xinchen (Frontiers in Oncology, 2019)
Salt-inducible kinase (SIK), which belongs to the sucrose non-fermenting 1/AMP-activated protein kinase family, was first discovered in the adrenal cortex of a rat on a high-salt diet. As an isoform of the SIK family, SIK2 modulates various biological functions and acts as a signal transmitter in various pathways. Compared with that in adjacent normal tissues, the expression of SIK2 is significantly higher in multiple types of tumors, which indicates its pivotal effect in oncogenesis. Studies on SIK2 have recently underlined its role in several signaling pathways, including the PI3K-Akt-mTOR pathway, the Hippo-YAP pathway, the LKB1-HDAC axis, and the cAMP-PKA axis. Moreover, a few small-molecule SIK2 inhibitors have been found to be able to rescue the oncogenicity of SIK2 during tumor development and reverse its abnormal activation of downstream pathways. In this mini-review, we discuss the results of in vivo and in vitro studies regarding the SIK2 mechanism in different signaling pathways, particularly their regulation of cancer cells. This work may provide new ideas for targeting SIK2 as a novel therapeutic strategy in tumor therapy.